Reproduction, distribution and abundance of Bothus constellatus (Pisces: Bothidae), in the Gulf of Tehuantepec, Mexico - Tapia-García, M (2000)
A total of 3 593 individuals of Bothus constellatus was captured during fíve oceanographic cruises carried out in the Gulf of Tehuantepec, Mexico. Its distribution, abundance, and reproduction pattems were stated by means of the analysis of the population parameters (i. e. density, biomass, weight and size average, visceral and gonadosomatic index, and maturity stages). B. constellatus is a typical demersal marine species, because it does not occur in estuaries, but oecurs near to them on the continental shelf. It is distributed in the Gulf of Tehuantepec in depths lesser than 60 m, with high abundan ce around the 40 m isobath, and in front of Mar Muerto Lagoon. During January and May the biomass and density were high. The size at fírst maturity of females is 10 1 mm total length, and maturation occurs fírst in zones influenced by estuarine processes. Reproduction and recruitrnent were detected in al! the collections.